1995
DOI: 10.1016/0896-6273(95)90251-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of an arginine residue in the human glycine receptor transforms β-alanine and taurine from agonists into competitive antagonists

Abstract: Agonist binding to the inhibitory glycine receptor (GlyR) initiates the opening of a chloride-selective channel that modulates the neuronal membrane potential. Point mutations of the GlyR, substituting Arg-271 with either Leu or Gln, have been shown to underlie the inherited neurological disorder startle disease (hyperekplexia). We show that these substitutions result in the redistribution of GlyR single-channel conductances to lower conductance levels. Additionally, the binding of the glycinergic agonists bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
142
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(164 citation statements)
references
References 37 publications
21
142
0
Order By: Relevance
“…This confirmed that at least a fraction of the channel protein was correctly inserted into the plasma membrane. The affinity for glycine (ECs0 = 18.6 pM) and the degree of agonist cooperativity as expressed by the Hill coefficient of channel activation (h = 4.2) were similar to values previously found for GlyR ~1 receptors expressed in HEK-293 cells (ECs0 = 29-100/zM, h = 1.6~4.2; see [4,5,18]). Preliminary single channel analysis in the outside-out patch clamp configuration revealed a main elementary conductance of 88 pS accompanied by subconductance states of 70 pS, 54 pS and 35 pS (N. Rundstr6m, unpublished results).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This confirmed that at least a fraction of the channel protein was correctly inserted into the plasma membrane. The affinity for glycine (ECs0 = 18.6 pM) and the degree of agonist cooperativity as expressed by the Hill coefficient of channel activation (h = 4.2) were similar to values previously found for GlyR ~1 receptors expressed in HEK-293 cells (ECs0 = 29-100/zM, h = 1.6~4.2; see [4,5,18]). Preliminary single channel analysis in the outside-out patch clamp configuration revealed a main elementary conductance of 88 pS accompanied by subconductance states of 70 pS, 54 pS and 35 pS (N. Rundstr6m, unpublished results).…”
Section: Discussionsupporting
confidence: 55%
“…A dissociation constant (Kd) for [3H]strychnine of 38 nM is within the range of values found for native spinal cord membranes and HEK-293 ceils transiently expressing ~1 GIyR (2-64 riM; see [19][20][21]18,15]). The maximal number of strychnine binding sites (Bma x = 71 pmol/mg) obtained with the Sf9 cell system, however, significantly exceeds the values found for spinal cord membranes and transfected HEK-293 cells (2.4-17 pmol/mg) by 4-to 30-fold (compare: [19,20,18,15]). Thus, infected Sf9 cells express the GlyR to much higher levels than native neurons or even transiently expressing mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…At both locations, the mutations result in the substitution of a positive charged residue. The effect of these mutations is to disrupt signal transduction, as inferred from the increases in EC 50 for glycine and the conversion of taurine from an agonist to an antagonist (8). This was also demonstrated at the single channel level for the K276E mutation (9).…”
mentioning
confidence: 70%
“…We infer from these results that these two loop 2 charged residues (Glu-53 and Asp-57) are involved in channel gating or the signal transduction process leading to channel gating. The conversion of taurine from an agonist to a partial agonist or an antagonist has previously been demonstrated by mutations within the M2-M3 linker, establishing this region as being involved in channel gating (8). The two charged residues in loop 7 (Lys-143 and Asp-148) were also shown to be involved in channel gating.…”
Section: Role Of Charged Residues In Loops 2 and 7 Of The Extracellulmentioning
confidence: 94%
“…In recombinantly expressed receptors, substitution of this residue weakens both the preference of the channel for states of high conductance 4,5 and the transition from closed to open states subsequent to glycine binding. 5,6 Also in recombinant receptors, the fluorescent signal of a thiol-reactive fluorophore bound to an introduced cysteine at this position is shifted to lower wavelengths, suggesting that during activation by glycine, the residue at position 271 enters a more hydrophobic environment. 7 In vivo, the decreased level of activation of R271-mutated α1 GlyRs results in neuronal hyperexcitability and the condition known as hyperekplexia or startle disease.…”
mentioning
confidence: 99%